2023
DOI: 10.1002/adhm.202300339
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle‐Mediated Transcutaneous Immunization: Potential in Nucleic Acid Vaccination

Abstract: Efforts aimed at exploring economical and efficient vaccination have taken center stage to combat frequent epidemics worldwide. Various vaccines have been developed for infectious diseases, among which nucleic acid vaccines have attracted much attention from researchers due to their design flexibility and wide application. However, the lack of an efficient delivery system considerably limits the clinical translation of nucleic acid vaccines. As mass vaccinations via syringes are limited by low patient complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…[58,59] From 2012 to 2022, 26 clinical trials have been conducted worldwide, according to relevant reports, more than 80% of participants preferred the microneedle patches for vaccination compared to traditional methods of drug administration. [60] In addition, electroporation has also been proven to vaccine delivery by increasing the electric field. However few clinical trials have shown the efficacy of physical transdermal delivery device nucleic acid vaccination.…”
Section: Microneedles Based Intelligent Transdermal Devicesmentioning
confidence: 99%
“…[58,59] From 2012 to 2022, 26 clinical trials have been conducted worldwide, according to relevant reports, more than 80% of participants preferred the microneedle patches for vaccination compared to traditional methods of drug administration. [60] In addition, electroporation has also been proven to vaccine delivery by increasing the electric field. However few clinical trials have shown the efficacy of physical transdermal delivery device nucleic acid vaccination.…”
Section: Microneedles Based Intelligent Transdermal Devicesmentioning
confidence: 99%
“…2B and 2C), verifying the thicknesses that can be penetrated were 508 µm. There is little doubt that the skin is divided into three main structural layers: stratum corneum, epidermis and dermis, while the stratum corneum with about 10-20 µm thick, is the skin's main barrier against drug penetration [42]. According to the above ndings, PLA MNs are adequate to pierce the stratum corneum and promote rapid drug absorption by creating micropore.…”
Section: The Insertion Properties Of Mnsmentioning
confidence: 99%
“…Then, the rat skin was folded and pretreated with PLA MNs. OCT hand-held probe was used to scan the skin of rats pretreated with MNs, and OCT images were collected to observe the insertion of MNs [42]. Then, to observe the healing of the MNs forming micropores, the MNs were removed after 30 s and observed micropores using a handheld microscope (Anmo electronics) and OCT.…”
Section: Rats Skin Insertion Of Mnsmentioning
confidence: 99%